2006
DOI: 10.1128/jb.188.9.3290-3298.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Transcriptional Activators SalA and SyrF, Which Are Required for Syringomycin and Syringopeptin Production byPseudomonas syringaepv. syringae

Abstract: Production of the phytotoxins syringomycin and syringopeptin by Pseudomonas syringae pv. syringae is controlled by the regulatory genes salA and syrF. Analysis with 70-mer oligonucleotide microarrays established that the syr-syp genes responsible for synthesis and secretion of syringomycin and syringopeptin belong to the SyrF regulon. Vector pMEKm12 was successfully used to express both SalA and SyrF proteins fused to a maltose-binding protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 79 publications
2
52
0
Order By: Relevance
“…4). This ORF shows 49% identity to syrF, which is involved in regulation of syringomycin biosynthesis (30,56). The role of this LuxR-type regulator in massetolide A biosynthesis is yet unknown, but preliminary results showed that overexpression of this gene resulted in an increased production of massetolide A in strain SS101 (data not shown).…”
Section: Organization Of the Massetolide Biosynthesis Genes And Identmentioning
confidence: 91%
“…4). This ORF shows 49% identity to syrF, which is involved in regulation of syringomycin biosynthesis (30,56). The role of this LuxR-type regulator in massetolide A biosynthesis is yet unknown, but preliminary results showed that overexpression of this gene resulted in an increased production of massetolide A in strain SS101 (data not shown).…”
Section: Organization Of the Massetolide Biosynthesis Genes And Identmentioning
confidence: 91%
“…SyrF transactivated the target NRPS promoter via the transaction of SalA. 22) Genome surveys of P. fluorescence PfO-1 and Pf-5, which are close relatives of MIS38, 17) indicated similar gene organization of syrF homologs located upstream of the putative NRPS genes for arthrofactin-like cyclic lipopeptides, suggesting conserved roles of SyrF-like proteins among related Pseudomonas spp. 6) Unlike transcriptional control by ArfF, normal expression of the genes for arthrofactin production was retained in the htpG::Tn5 mutant (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…27,34) transcription factor 21) and an evident homolog of SyrF. 22) The syrF and salA genes for the LuxR-family proteins locate in the NRPS operon, responsible for the production of two lipopeptides, syringomycin and syringopeptin, in P. syringae pv. syringae B301D.…”
Section: Discussionmentioning
confidence: 99%
“…19) SalA is an essential upstream regulator that positively controls the expression of the syr and syp synthetase genes and the syrF regulatory gene. 20) Our previous study indicated that loss of the arfF function (arfF::Tn5) reduces arthrofactin production. 6) arfF is the evident homolog of syrF and locates just upstream of the arthrofactin synthetase operon (Fig.…”
Section: Transcriptional Control Of Arthrofactin Productionmentioning
confidence: 99%
“…C, Biofilm formation on the surface of polypropylene tube. After cultivation for 4 d at 20 C, the area of the biofilm ring was stained with 0.1% w/v crystal violet (CV) solution and observed by light microscope. CV staining was conducted at different times (0.5, 1, 2, 3, 4, and 5 d), and then the CV adhering to the biofilm was dissolved in 95% ethanol, the absorbance of which at 590 nm was measured.…”
Section: )mentioning
confidence: 99%